Determinants of urban household concentration in Uganda: a regional analysis using 2023/2024 survey data.” - Jesse Magezi (Uganda Christian University, 2026)
Urbanization can also be noted as one of the most influential structural changes that are defining the developing economies in the twenty first century. Nonetheless, geographical distribution of urban households may be mirroring profound region inequalities and not nationwide transition. The present research investigates a model of urban household concentration in Uganda by employing codified 2023 large-scale nationally representative survey statistics on households. In particular, it examines whether the status of region and time of year affects the likelihood of a household to be urban greatly. The paper relies on the structural transformation theory and spatial inequalities frameworks to identify how a binary logistic regression model, which is estimated using Maximum Likelihood Estimation, is used to analyse the data. These findings indicate that the regional location has been found to be the main determinant of the urban classification. Compared to the Central region, the Northern, Eastern, and Western regions have households with far lesser odds of being urban confirming excellent spatial concentration. Conversely, the annual change between the 2023 and 2024, monthly seasonality are statistically insignificant, as it implies that urban settlement patterns in Uganda are stable as opposed to volatile in terms of time. The results offer micro-economic data of geographical differences in settlement patterns and support the significance of spatially balanced growth techniques. The paper determines that the key elements to implement in promoting sustainable urban transformation in Uganda include regional investment, mastering of secondary urban centres and mandatory coordination of regional planning systems.
Undergraduate